Pregunta
upstudy study bank question image url

Decompose \( \frac{x^{2}-3}{(x-1)\left(x^{2}+1\right)} \)

Ask by Santiago Mathis. in South Africa
Feb 18,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( \frac{x^{2}-3}{(x-1)(x^{2}+1)} = -\frac{1}{x-1} + \frac{2x+2}{x^{2}+1} \)

Solución

We want to express   (x² – 3) / [(x – 1)(x² + 1)] as a sum of simpler fractions. Since the denominator factors into a linear term (x – 1) and an irreducible quadratic (x² + 1), we write the partial fractions in the form:   A/(x – 1) + (Bx + C)/(x² + 1). Step 1. Write the identity:   (x² – 3)/[(x – 1)(x² + 1)] = A/(x – 1) + (Bx + C)/(x² + 1). Step 2. Clear the fractions by multiplying both sides by (x – 1)(x² + 1):   x² – 3 = A(x² + 1) + (Bx + C)(x – 1). Step 3. Expand the right-hand side:   A(x² + 1) = Ax² + A.   (Bx + C)(x – 1) = Bx² – Bx + Cx – C = Bx² + (C – B)x – C. Thus,   x² – 3 = (A + B)x² + (C – B)x + (A – C). Step 4. Equate coefficients of corresponding powers of x:   Coefficient of x²: A + B = 1.   Coefficient of x:  C – B = 0.   Constant term:   A – C = -3. From C – B = 0, we have C = B. Substitute C = B into A – C = -3:   A – B = -3  → A = B - 3. Then substituting A = B - 3 into A + B = 1:   (B - 3) + B = 1  → 2B - 3 = 1  → 2B = 4  → B = 2. Thus,   A = 2 - 3 = -1,   C = B = 2. Step 5. Write the final decomposition:   (x² – 3)/[(x – 1)(x² + 1)] = -1/(x – 1) + (2x + 2)/(x² + 1). We can also factor the numerator of the second term:   (2x + 2) = 2(x + 1), so another acceptable answer is:   (x² – 3)/[(x – 1)(x² + 1)] = -1/(x – 1) + [2(x + 1)]/(x² + 1). This is the required partial fractions decomposition.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To decompose the given expression \( \frac{x^{2}-3}{(x-1)(x^{2}+1)} \), we can express it in the form: \[ \frac{A}{x-1} + \frac{Bx + C}{x^{2} + 1} \] where \( A \), \( B \), and \( C \) are constants to be determined. Multiply both sides by the denominator \( (x-1)(x^{2}+1) \): \[ x^{2}-3 = A(x^{2}+1) + (Bx + C)(x-1) \] Now, expand the right side: \[ x^{2}-3 = A(x^{2}+1) + (Bx^{2} - Bx + Cx - C) \] \[ = Ax^{2} + A + Bx^{2} + (C-B)x - C \] \[ = (A + B)x^{2} + (C-B)x + (A - C) \] Now we match coefficients from both sides of the equation: 1. For \( x^{2} \): \( A + B = 1 \) 2. For \( x \): \( C - B = 0 \) 3. Constant term: \( A - C = -3 \) Now we solve this system of equations: From \( C - B = 0 \), we have \( C = B \). Substituting \( C = B \) into \( A - C = -3 \): \[ A - B = -3 \quad \text{(1)} \] Now substituting \( C = B \) into \( A + B = 1 \): \[ A + B = 1 \quad \text{(2)} \] Now we can solve these two equations. From equation (2): \[ A = 1 - B \] Substituting this expression for \( A \) into equation (1): \[ 1 - B - B = -3 \] \[ 1 - 2B = -3 \] \[ -2B = -4 \] \[ B = 2 \] Using \( B = 2 \) in equation (2): \[ A + 2 = 1 \implies A = -1 \] And since \( C = B \): \[ C = 2 \] Thus, we have found the values: \[ A = -1, \quad B = 2, \quad C = 2. \] The partial fraction decomposition is: \[ \frac{x^{2}-3}{(x-1)(x^{2}+1)} = \frac{-1}{x-1} + \frac{2x + 2}{x^{2}+1}. \] So the final answer is: \[ \frac{-1}{x-1} + \frac{2x + 2}{x^{2}+1}. \]

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad